Optimal solution for the single-beam bridge crane girder using the Moth-Flame algorithm - Pavlović, Goran V.; Savković, Mile M.; Zdravković, Nebojša B.; Marković, Goran Đ.; Mladenović, Predrag Z. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: The paper analyses and optimizes the welded I-girder of the single-beam bridge crane with a U-profile as the top flange. This solution is to provide a lighter carrying structure, so the main goal is to minimize the weight of the main girder, i.e., the cross-sectional area while fulfiling the requirements defined by national standards and geometric constraints. Methods: The Moth-Flame Optimization (MFO) algorithm was chosen for solving this single-objective multi-criteria optimization task using MATLAB. Also, the results were verified by using the Finite Element Analysis (FEA). Results: The proposed girder shape is justified in examples of real solutions of single-beam bridge cranes and the previous research results. In this case, significant savings in the material and better results are achieved compared to the examples from the previous research. Conclusion: The proposed girder shape, methodology, the optimization algorithm and the achieved savings fully justify this research. Furthermore, this algorithm enables the application of many constraint functions, whereby the optimal values of numerous variables are obtained in a relatively short period. Therefore, it would not be possible to find the solution for that engineering task by applying analytical optimization methods.